A Repertoire of Marketers' Trust-Building Strategies Within The Sales-Marketing Interface. Issue 3 (3rd July 2017) - Malshe, Avinash; Al-Khatib, Jamal A.
Abstract : Examining how sales and marketing personnel interrelate is analogous to studying intergroup cooperation wherein two groups – sales and marketing – are required to work cooperatively to achieve specific firm-level objectives. While extensive literature in psychology and management has implied that trust is an important precursor of enhanced intergroup cooperation, no extant scholarly work has explicated the specific activities sales and marketing personnel may engage in to build trust within the sales-marketing interface (SMI). We use qualitative methodology and in-depth interview data collected from 29 sales and marketing executives in Saudi Arabia to investigate the specific activities that may help marketers build trust with their sales counterparts and signal to them that they are a dependable partner. Study findings suggest that when marketers (a) act as salespeople's ambassadors to senior leaders; (b) stay invested in salespeople's success; and (c) act as a semipermeable barrier between salespeople and the leadership, they are able to engender trust with salespeople. In addition to providing a preliminary thesis regarding how marketers may build trust within SMI, study findings highlight how the specific trust-building activities may contribute to strategic phenomena such as marketing-strategy making, sales buy-in of marketing strategies, and organizational learning.